Abundance of Pollinator Insect (Forcipomyia spp .) of Cocoa Under Some Shade Trees - Fakhrusy Zakariyya; Endang Sulistyowati; Dwi Suci Rahayu (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Cocoa production is affected by cocoa flowering and fruiting. The factor affects fruit seeting is pollinator agent such as Forcipomyia spp. Until now, information concerning population dynamics of Forcipomyia in some models of cocoa shading trees remains limited. This research was studied to observe the population dynamics of Forcipomyia spp. in some models of cocoa shading trees, namely lamtoro (Leucaena sp.), krete (Cassia surithensis) and areca nut (Areca catechu) in two main season of rainy and dry seasons. The research was conducted in Kaliwining research station of Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, by surveying the existing cocoa under different types of shading trees as mentioned above. The insects were observed using modified sticky trap method, whilst micro climate condition was also observed. The highest population was in January (rainy season) under Leucaena spp. shade tress and the lowest population was in October under all type of the shading trees. There was no relationship between microclimate condition under cocoa trees (temperature, RH and light intensity) and Forcipomyia spp. population (r = 0.08 and 0.04).